METAL FRAME CONSTRUCTIONS FOR ONE-STOREYED INDUSTRIAL BUILDINGS - Pershakov, Valery M.; Borovsky, Roman V.; Gorbenko, Olexandra O.; Zavgorodny, Dmytro V. (Proceedings of National Aviation University, 2008)
Generalization and analysis of designing experience and construction of one-storey industrial buildings in metal frame constructions are conducted.